2016
DOI: 10.3916/c46-2016-06
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of School Climate and Family Climate among Adolescents Victims of Cyberbullying

Abstract: El ciberacoso es un fenómeno de creciente preocupación social que afecta cada vez más a niños y adolescentes de todos los paí- ses desarrollados. A diferencia de la considerable literatura que hay sobre las relaciones entre el acoso escolar y el contexto familiar y escolar, todavía hay pocos trabajos sobre la influencia de estos entornos sociales en el problema del ciberacoso. Mediante una metodología cuantitativa, el objetivo principal del presente estudio fue analizar la influencia del contexto escolar y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
74
1
29

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 31 publications
14
74
1
29
Order By: Relevance
“…The technological changes, along with the appearance and modification of new cyber-victimization behaviors, as well as the severe consequences of cyber-bullying for the victim's psychological wellbeing (Ortega-Barón et al 2016;Nocentini et al 2018), suggest the need for updated and reliable instruments that allow its adequate measurement. In this regard, this study has found empirical evidence that supports the scale's validity, factor structure, internal consistency, and convergent validity with theoretically related external variables.…”
Section: Discussionmentioning
confidence: 99%
“…The technological changes, along with the appearance and modification of new cyber-victimization behaviors, as well as the severe consequences of cyber-bullying for the victim's psychological wellbeing (Ortega-Barón et al 2016;Nocentini et al 2018), suggest the need for updated and reliable instruments that allow its adequate measurement. In this regard, this study has found empirical evidence that supports the scale's validity, factor structure, internal consistency, and convergent validity with theoretically related external variables.…”
Section: Discussionmentioning
confidence: 99%
“…Cyberbullying is a phenomenon of social growth possessed by children and adolescents in their development (Ortega-barón, Buelga, & Cava, 2016). Bullying behavior is often repeated, potentially repeated over time (Center for Disease Control, 2014).…”
Section: Eating Behaviormentioning
confidence: 99%
“…This idea is reinforced by the exhaustive work done in 33 countries from 2002 to 2010 with students aged 10–15, which concluded that countries which have made decisions concerning the social problem of bullying and have carried out specific actions in school contexts have reduced both occasional and chronic victimization (Chester et al, 2015). Another recent study included the family along with the school in the bullying/cyberbullying prevention measures (Ortega et al, 2016). Beyond that, even the need to talk about citizenship is suggested, as the relationship between bullying and cyberbullying with homophobia, sexism, racism and other discriminatory situations, which are reinforced and modeled by the adult society, has been demonstrated, and structured action leading to the prevention of this phenomenon must start when schooling begins (Cabra and Marciales, 2015).…”
Section: Introductionmentioning
confidence: 99%